Illumination Estimation Based Color to Grayscale Conversion Algorithms - Wei Hong Lim; Nor Ashidi Mat Isa (IAES Indonesia Section, 2014)
In this paper, a new adaptive approach, namelythe illumination estimation approach is introduced into the colorto grayscale conversion technique. In this approach, someassumptions will be made to calculate the weight contribution ofred, green, and blue components during the conversion process.Two color to grayscale conversion algorithms are developedunder this approach, namely the Gray World Assumption Colorto Grayscale Conversion (GWACG) and Shade of GrayAssumption Color to Grayscale (SGACG) conversion algorithms.Based on the extensive experimental results, the proposedalgorithms outperform the conventional conversion techniquesby producing resultant grayscale images with higher brightness,contrast, and amount of details preserved. For this reason, theseproposed algorithms are suitable for pre- and post- processing ofdigital images.